PENYUSUNAN LAPORAN KEUANGAN UMKM BERDASARKAN STANDAR KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK-EMKM) PADA UMKM IKAN MAS ARAFI DI MUSTIKA JAYA BEKASI - ATIKA RAHMI (Institut Bisnis Muhammadiyah Bekasi, 2022)
One of the drivers of economic development in Indonesia is the existence of Micro, Small, and Medium Enterprises. The Indonesian economy cannot be separated from businesses that are run by individuals or groups and also MSMEs, which in fact are the majority of Indonesians' economic activities. Where the economic activities of these MSMEs have participated in creating jobs in Indonesia so as to reduce unemployment. The problem that often occurs is that Micro, Small, and Medium Enterprises are unable to produce financial reports. In terms of financial reports, it is very important to predict the financial flows of a company on a small scale. MSME financial reports are still very simple and done manually and the financial reports are not in accordance with SAK- EMKM. The purpose of this Community Service activity is to compile financial reports at Arafi Goldfish company in accordance with financial accounting standards. The research method used is descriptive qualitative. while the primary data sources are interviews, observations, proof of transactions, and documentation. From the research conducted, it can be concluded that the financial statements of micro, small, and medium-sized Ikan Mas Arafi are in the form of balance sheets and profit and loss reports, as well as notes on financial statements. With these findings, it is hoped that it can provide information for the owner of Arafida's goldfish MSME business in applying the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK-EMKM).